(Re)konstruowanie pamięci o Rewolucji w nowym kinie rumuńskim - Syska, Rafał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
(Re)construction of Memories of the Revolution in Contemporary Romanian Cinema The article examines contemporary Romanian cinema from a postmemory methodological perspective (based on the ideas of Marianne Hirsch, Dominick LaCapra and others). In the first section, a few key aspects of this concept are presented, and developed as a methodology for research on contemporary cinema, and then the history of the 1989 Revolution in Romania is outlined. In the second part of the text, the process of falsifying the Revolutionarch on contemporary cinema, and then the history of ctivity in the Ceauty in era. In the third section, contemporary topics in Romania are described, with emphasis on traumas in today’s society and the sins committed in the previous era.